Using spirometry for screening and diagnosis of chronic respiratory diseases in primary health care: findings from a community health project in rural India - Gajanan Sakhare; Yogesh Chitte; Radha Munje; Shardul Joshi; Meenakshi Bhakare (Journal of Global Health Reports)
# Background Chronic respiratory diseases (CRDs) such as Chronic obstructive pulmonary disease (COPD), Asthma and post-tuberculosis lung disease (PTLD) are a growing public health concern in India. Early diagnosis and management of CRDs require a good quality spirometry test, a technician to conduct spirometry and a chest physician to interpret the results. In India, these are not available at the primary care level. This study reports the feasibility of a large-scale CRD diagnosis and management program in primary care using a unique point-of-care spirometry solution, Briota PFT in a Box™. # Methods A community-based cross-sectional study was conducted among 15,602 adults in Dindori Taluka (subdivision), Nashik, Maharashtra state. This study was part of a holistic CRD diagnosis and management program SAVE™ (Spirometry Assisted Virtually Early). Make In India point of care solution Briota PFT in a Box™ was used. A House‐to‐house community-based assessment checklist (CBAC) survey, 4-parameter spirometry test, 15-parameter pre and post-bronchodilator spirometry test and a software-assisted medical examination by the medical officer at primary care were conducted. Software was used to generate CRD diagnosis and lung health score (LHS™). The diagnosis was verified by the chest physician. Confirmed diagnosed patients were provided treatment and offered a patient support program. Interviews were conducted with the patients, nurses, doctors and public health officials for understanding feasibility and documenting learning from program SAVE™. # Results Out of 15,602 adults surveyed, total 4,937 (31.6%) were identified as “CRD high risk”. 1231 participants based on medical examination, spirometry tests and software analysis were identified as CRD candidates by medical officers at primary care. 1154 participants out of 15,602 (7.4%) were confirmed diagnosed as CRD patients post independent evaluation by chest physicians. At the time of follow-up, 537 patients (75% of 712 patients enrolled in patient support program) reported improvement in symptoms and high satisfaction with the program. District health officer, Medical officers, nurses, Accredited Social Health Activist (ASHA) from the primary health care centers confirmed ease of use and feasibility of using Briota PFT in a Box™ in program SAVE™. Outcome and learning from program SAVE™ was documented and submitted to Ministry of Health and Family Welfare Government of India. # Conclusions CRD diagnosis and management in large scale settings in primary healthcare level using a point of care spirometry solution Briota PFT in a Box™ is highly feasible.